Treatment of developmental dysplasia of the hip before walking: results of closed reduction and immobilization in hip spica cast - Aksoy, M. Cemalettin; Özkoç, Gürkan; Alanay, Ahmet; Yazıcı, Muharrem; Özdemir, Nasır; Surat, Adil (The Turkish Journal of Pediatrics, 2002)
We retrospectively evaluated 200 hips of 129 patients with the diagnosis of developmental dysplasia of the hip treated with closed reduction and hip spica cast. There were 153 female and 47 male hips in the group. The mean age of the patients at the time of the reduction were six (range. 2-13) months and mean follow-up was 51 (range: 16-240) months. All the patients were treated with closed reduction and were immobilized in hip spica cast. The mean time of immobilization in the cast was 102 (range: 45-190) days. Avascular necrosis was observed in 15% of the hips. Clinical and radiological end results of the patients were evaluated with modified McKay criteria and Severin classification. Eighty-two percent of the patients had satisfactory results according to modified McKay criteria and 76% of the patients according to Severin classification. The most important parameters affecting the end result were pre-reduction location of the hip, pre-operative acetabular index values and avascular necrosis. Based on the results of this study, treatment of developmental hip dysplasia with closed reduction and hip spica cast is a relatively safe and effective method.